Vier Jahre Eurokrise: Wege zu neuem Systemvertrauen - Nicolaus Heinen (Wirtschaftsdienst, 2013)
Die Eurokrise und die Reaktion der Politik auf sie hat das Vertrauen der Bevölkerung in die gemeinsame Währung erschüttert. Um das Vertrauen in das Eurosystem neu aufzubauen, sind verschiedene Maßnahmen erforderlich: Regeln für Verlässlichkeit und gesellschaftliche Akzeptanz, Aussichten auf Wachstum und Teilhabe, und nicht zuletzt eine Debatte über gemeinsame europäische Werte. – – Political gridlock, violations of European law and inconsistent political communication have turned the euro crisis into a crisis of confidence in public policy. To re-establish trust in the system, Europe needs a comprehensive approach consisting of three elements. First, rules can invigorate societies if they provide for cross-border competition in a revived single market and abstain from top-down provisions. Second, new growth perspectives - e.g. by reassigning major parts of the EU budget - can enhance the selfconfidence of societies. And finally, a pan-European debate on common goals and values can help answer the essential question of Europe's sense and purpose. As the euro can only ever enjoy as much trust as the institutions governing the euro area, the solution of the European confi dence crisis is crucial to the fate of the common currency.
Keywords: E60; F55; Z18; 330; Euro; Europäische Wirtschafts- und Währungsunion; Öffentliche Schulden; Systemrisiko; Öffentliche Meinung; Vertrauen; Soziale Werte; EU-Staaten